Práticas de resistência à opressão dos corpos na Educação Infantil - Machado da Silva, Hilary (Universidade Federal de São Carlos, 2021)
This qualitative, bibliographical and field research sought to answer the following problem-question: which ways of acting pedagogically with the movement in day care center favor the fight against adultcentrism that both oppresses and prohibits the movement as well as imposes and obliges? Its objective was to understand the central elements of a humanizing practice that fosters the importance of the body and movement, seeking to investigate how these processes of oppression take place. The first chapter has a Memorial that recounts the author's encounter with the theme. Chapter II presents the methodological procedures. Chapter III comprises the theoretical framework, being organized into three topics that address the concept of child today, the oppression of the bodies and the importance of body movement in the daily routine of daycare. The Data Analysis Chapter presents reflections and problematizations of moments experienced during ten months of internship in a municipal day care center in Sorocaba-SP with 3-4 year-old children, in the light of the bibliography studied in the theoretical framework. As a result, it was found: that Early Childhood Education professionals face problems of overcrowding in rooms, which have reduced space and environments that are not designed for babies; that the daycare routine is exhausting for babies and that their bodies are heavily disciplined in the institutional routine; that the daycare is constituted as an environment of surveillance and regulation also for educators, with the construction of a hierarchical structure of power that assumes absolute control of all the professionals' actions. It was possible to understand the harm caused by oppressive practices and the need for a pedagogical approach that is sensitive to the importance and respect for the bodies and the movement.
Resistance practices to the oppression of the bodies in early childhood education
Keywords: Corpo; Body; Movimento; Movement; Formação de professores; Teacher education; Educação infantil; Early childhood education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO